Engineering Multi‐Cellular Spheroids for Tissue Engineering and Regenerative Medicine. Issue 23 (30th July 2020) - Kim, Se‐jeong; Kim, Eun Mi; Yamamoto, Masaya; Park, Hansoo; Shin, Heungsoo
Abstract: Multi‐cellular spheroids are formed as a 3D structure with dense cell–cell/cell–extracellular matrix interactions, and thus, have been widely utilized as implantable therapeutics and various ex vivo tissue models in tissue engineering. In principle, spheroid culture methods maximize cell–cell cohesion and induce spontaneous cellular assembly while minimizing cellular interactions with substrates by using physical forces such as gravitational or centrifugal forces, protein‐repellant biomaterials, and micro‐structured surfaces. In addition, biofunctional materials including magnetic nanoparticles, polymer microspheres, and nanofiber particles are combined with cells to harvest composite spheroids, to accelerate spheroid formation, to increase the mechanical properties and viability of spheroids, and to direct differentiation of stem cells into desirable cell types. Biocompatible hydrogels are developed to produce microgels for the fabrication of size‐controlled spheroids with high efficiency. Recently, spheroids have been further engineered to fabricate structurally and functionally reliable in vitro artificial 3D tissues of the desired shape with enhanced specific biological functions. This paper reviews the overall characteristics of spheroids and general/advanced spheroid culture techniques. Significant roles of functional biomaterials in advanced spheroid engineering with emphasis on the use of spheroids in the reconstruction of artificial 3D tissue for tissue engineering are also thoroughly discussed. Abstract : Multi‐cellular spheroids are being widely utilized as implantable therapeutics and various tissue models in tissue engineering. Recently, spheroids are engineered to fabricate in vitro artificial 3D tissues. This paper reviews characteristics and various fabrication methods of spheroid. Furthermore, advanced spheroid engineering techniques using functional biomaterials are also introduced.